2021
DOI: 10.3390/met11040578
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Hot-Dip Galvanized DP Steels via Artificial Neural Networks and Multi-Objective Genetic Optimization

Abstract: This modeling and optimization study applies a non-linear back-propagation artificial neural network, commonly denoted as BPNN, to model the most important mechanical properties such as yield strength (YS), ultimate tensile strength (UTS) and elongation at fracture (EL) during the experimental processing of hot-dip galvanized dual-phase (GDP) steels. Once the non-linear BPNN is properly trained, the most important variables of the continuous galvanizing process, including initial/first cooling rate (CR1), hold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The model includes an equation of state implemented in the form of an artificial neural network (ANN) and trained according to MD simulations of uniform isothermal stretching/compression of representative volumes of copper; the equation of state is also used to calculate the shear modulus. Currently, ANNs are widely used in materials science [94][95][96]. In the present research, application of the ANN was more of a methodological issue, because there are a number of reliable equations of state for pure copper.…”
Section: Discussionmentioning
confidence: 93%
“…The model includes an equation of state implemented in the form of an artificial neural network (ANN) and trained according to MD simulations of uniform isothermal stretching/compression of representative volumes of copper; the equation of state is also used to calculate the shear modulus. Currently, ANNs are widely used in materials science [94][95][96]. In the present research, application of the ANN was more of a methodological issue, because there are a number of reliable equations of state for pure copper.…”
Section: Discussionmentioning
confidence: 93%
“…This approach greatly expands the range of alloys that can be modelled, as well as the complexity of these alloy compositions, and provides predictions that are both quick and reliable. Recent studies have had good success with using JMatPro to predict the CCT behaviour of steels [26,27]; however, direct comparisons with experimental CCTs showed some discrepancies in the study by Krbat'a et al [27], with small deviations observed between T s and T f values and critical cooling rates. These differences were concluded to be a result of variations in chemical composition, which is a reasonable assumption.…”
Section: Introductionmentioning
confidence: 99%
“…In [15,16], different ML models are compared to predict the nose point and the TTT diagram for pearlitic steels and galvanized dual-phase steels. To compare the proposed models, different metrics are used, e.g., the correlation coefficient (R2), the root mean square error, and the mean absolute percent error (MAPE).…”
Section: Introductionmentioning
confidence: 99%